Development and validation of a couples measure of biased responding: The Marital Aggrandizement Scale. - O'Rourke, Normand Patrick. (University of Ottawa (Canada), 2001)
More than 30 years ago, Edmonds recognized the need for a couples measure of biased responding. Like other categories of self-report instruments, marital measures are believed to be highly susceptible to distortion. Edmonds developed the Marital Conventionalization Scale (MCS) to measure overly positive appraisal of one's marriage. Subsequent research, however, has failed to confirm that the MCS is a valid measure of socially desirable responding. In keeping with this observation, the current study set out to develop a new couples measure of biased responding. An extended pool of items included statements from the existing MCS, additional items from Edmonds' original validation study as well as items written specifically for this study. The scoring protocol for the revised measure was also changed from a true/false, forced choice format to a 7-point, Likert-type scale to increase measurement sensitivity. Item analyses were performed among a random subgrouping of older adults ( n = 200). Various a priori inclusion criteria were applied from which a set of 18 items was selected. Three phases of validation research establish the reliability and validity of this measure among an international sample of older married adults (n = 350). The concurrent and discriminant validity of this scale is demonstrated relative to separate measures of biased responding, marital satisfaction, and psychological well-being respectively. Indices of internal consistency as measured by Cronbach's alpha range from alpha = .84 to alpha = .87. Test-retest reliability over an average interval of 43 days is calculated as r(102) = .75. This coefficient compares favourably to those obtained for other indices of biased responding among these same participants. Consistent with existing research, it is proposed that the new instrument henceforth be known as the Marital Aggrandizement Scale (MAS). The challenge remains to identify factors associated with the etiology and maintenance of marital aggrandizement. Is this construct particular to older adults within long-term relationships or common to all stages of romantic relationships irrespective of duration? Subsequent research is required to identify correlates and predictors of marital aggrandizement across populations, over time.
Keywords: Psychology, Social.